Generating three-parameter sensor - Filinyuk, M. A.; Lishchinska, L. B.; Lazarev, O. O.; Tkachuk, Ya. S. (Technology and design in electronic equipment, 2014)
Generating sensors provide the possibility of getting remote information and its easy conversion into digital form. Typically, these are one-parameter sensors formed by combination of a primary transmitter (PT) and a sine wave generator. Two-parameter sensors are not widely used as their implementation causes a problem with ambiguity output when measuring the PT. Nevertheless, the problem of creating miniature, thrifty multi-parameter RF sensors for different branches of science and industry remains relevant. Considering ways of designing RF sensors, we study the possibility of constructing a three-parameter microwave radio frequency range sensor, which is based on a two-stage three-parameter generalized immitance convertor (GIC). Resistive, inductive and capacitive PT are used as sensing elements. A mathematical model of the sensor, which describes the relation of the sensor parameters to the parameters of GIC and PT was developed. The basic parameters of the sensor, its transfer function and sensitivity were studied. It is shown that the maximum value of the power generated signal will be observed at a frequency of 175 MHz, and the frequency ranges depending on the parameters of the PT will be different. Research results and adequacy of the mathematical model were verified by the experiment. Error of the calculated dependences of the lasing frequency on PT parameters change, compared with the experimental data does not exceed 2 %. The relative sensitivity of the sensor based on two-stage GIC showed that for the resistive channel it is about 1.88, for the capacitive channel –1,54 and for the inductive channel –11,5. Thus, it becomes possible to increase the sensor sensitivity compared with the sensitivity of the PT almost 1,2–2 times, and by using the two stage GIC a multifunctional sensor is provided.